Reactions of dichlorozirconocene with nitrogen containing heterocycles and related compounds - Ünal, A. Özge Akdeniz. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1999., 1999)
In this study the reaction of 16 e- system, dichlorobiscyclopentadienyl- zirconium(IV) with N-containing, S-containing and thioamide containing ligands were studied. In the presence of a non-coordinating solvent, CH2Cl2, thioacetamide coordinated to Cp2ZrCl2 through C=S unit with participation of the NH group. This complexation was proved by the new bands appearing in Zr-N and Zr-S stretching region, also by the blue shift of thioamide band I and the red shift of thioamide band IV of thioacetamide. Deprotonated ethanethiol with Cp2ZrCl2 gave a dimeric complex with the formula (Cp2ZrClSCH2CH3)2. Without deprotonation ethanethiol did not coordinate to Cp2ZrCl2.
Keywords: Heterocyclic compounds.